Pemanfaatan Sosial Media Sebagai Wujud Inovasi Dalam Pelayanan Publik Oleh Ombudsman Ri Bengkulu - Fitria Yuliani; Rekho Adriadi; Linda Safitra (Universitas Merdeka Madiun, 2020)
The use of social media today is not only functioned for personal interests, but also for the benefit of groups, organizations, and state institutions in terms of public services as conducted by the Ombudsman RI Bengkulu who utilize social media as a medium of public service in Bengkulu province. It is interesting to study about the new